(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
The purpose of this study is to explore the construction of the public relations system at the Regional Inspectorate of South Sulawesi Province, in communication governance and public relations challenges in the implementation of communication governance. This study used a qualitative research method with a descriptive approach. Sources of data obtained are primary data and secondary data. Data collection techniques are using interviews, observation and documentation, using the theory of excellence. Excellence theory in public relations is a theory that dominates public relations studies so that it is considered a normative theory, namely as a standard measure of effective public relations. The results in research on the construction of the public relations system, communication governance at the Regional Inspectorate of South Sulawesi Province are in the form of a digital platform system in the form of the SP4N-LAPOR application and a service center system, namely SMS to number 1708. Where this system is based at the Governor’s Office and managed by the Ministry of Administrative and Bureaucratic Reform. The challenges in the implementation of communication governance at the Regional Inspectorate of South Sulawesi Province are the limited human resources and communication governance systems. Where this system is based at the Governor’s Office and managed by the Ministry of Administrative and Bureaucratic Reform. The challenges in the implementation of communication governance at the Regional Inspectorate of South Sulawesi Province are the limited human resources and communication governance systems. Where this system is based at the Governor’s Office and managed by the Ministry of Administrative and Bureaucratic Reform. The challenges in the implementation of communication governance at the Regional Inspectorate of South Sulawesi Province are the limited human resources and communication governance systems.